Ethical Challenges in AI-Driven Cybersecurity Decision-Making - Emmanuel Cadet; Edima David Etim; Iboro Akpan Essien; Joshua Oluwagbenga Ajayi; Eseoghene Daniel Erigha (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The integration of artificial intelligence (AI) into cybersecurity decision-making has significantly enhanced the speed, accuracy, and scalability of threat detection, incident response, and risk assessment. However, the rapid adoption of AI-driven systems also introduces complex ethical challenges that can undermine trust, fairness, and accountability in security operations. This paper examines the critical ethical considerations in AI-driven cybersecurity decision-making, focusing on transparency, bias, privacy, accountability, and the human–machine interface. A central concern is the opacity of many AI models, particularly deep learning architectures, which can produce high-accuracy outputs without providing interpretable reasoning, complicating both operational trust and legal admissibility. Algorithmic bias presents another significant risk, as skewed training data or flawed model design may lead to discriminatory threat prioritization or disproportionate false positives/negatives against specific user groups or regions. The integration of AI in cybersecurity also raises privacy concerns, especially when large-scale data aggregation and monitoring are used to train or operate security models, potentially infringing on user rights and regulatory compliance mandates such as the GDPR or CCPA. Accountability becomes a pressing issue when AI systems make autonomous or semi-autonomous decisions in time-sensitive contexts, blurring the lines of responsibility between human operators, developers, and organizational leadership. Additionally, overreliance on AI may erode human expertise, leading to complacency or inadequate oversight, while adversaries exploit AI vulnerabilities through data poisoning, adversarial inputs, or model inversion attacks. The paper emphasizes the necessity of embedding ethical principles into the AI development lifecycle, including fairness-by-design, explainable AI (XAI) integration, continuous auditing, and maintaining a human-in-the-loop for critical cybersecurity decisions. It also advocates for multi-stakeholder governance frameworks that balance technological efficiency with societal values, ensuring that AI-driven cybersecurity tools operate within legal, cultural, and ethical boundaries. By addressing these challenges proactively, organizations can harness the advantages of AI while safeguarding against ethical pitfalls that could compromise both security outcomes and public trust.